Lifelong learning education for Fardhu ‘Ayn skill and knowledge: an analytical study from the Bustan ‘Ilm project of CENTRIS IIUM - Fatah Yasin, Raudlotul Firdaus; Nik Abdullah, Nik Md Saiful Azizi (Faculty of Islamic Studies, UKM, 2024)
The research “Lifelong Learning Education for Fardhu ‘Ayn Skill and Knowledge: An Analytical Study from the Bustan 'Ilm Project of CENTRIS IIUM” explores the role of lifelong learning in enhancing Fardhu ‘Ayn skills and knowledge. The study focuses on the Bustan 'Ilm project, an initiative by the Centre for Islamisation at the International Islamic University Malaysia (CENTRIS IIUM), aimed at promoting continuous learning among the elderly Muslims. This study employs a qualitative research approach, specifically adopting a library-based technique to examine existing literature. Additionally, semi-structured interviews were conducted with respondents, and thematic analysis was used to analyse the collected data. The research highlights the importance of Fardhu ‘Ayn in the holistic development of an individual and society. The findings of this study show that lifelong learning is crucial as one way to acquire and enhance Fardhu ‘Ayn skills and knowledge especially for the preparation to obtain Husnul Khatimah. Hence, through one of the initiatives established by the CENTRIS IIUM, the foundation of the Bustan ‘Ilm project is seen as one of the solutions provided and offers the Islamic-based learning syllabus. The study concludes that the Bustan ‘Ilm Project is a valuable initiative that contributes to the Islamisation mission of IIUM and the empowerment of elderly citizens in the Muslim community.